Union of Comoros : Detailed Assessment Report of Anti-Money Laundering and Combatting the Financing of Terrorism - International Monetary Fund (World Bank, Washington, DC, 2013)
The assessment of the anti-money laundering and combating the financing of terrorism (AML/CFT) system of the Union of the Comoros was based on the 2003 Forty Recommendations and the 2001 Nine Special Recommendations developed by the FATF (Financial Action Task Force). It was prepared according to the 2004 AML/CFT Methodology, as updated in October 2008. The assessment was based on laws, regulations, and other documents provided by the Union of the Comoros, as well as information gathered by the assessment team during its on-site visit of May 6-20, 2009 and following the mission. During the course of its visit, the assessment team met with leaders and representatives from competent governmental agencies and the private sector. The assessment was performed by a team made up of International Monetary Fund (IMF) staff, an expert acting under the supervision of the IMF, and an expert acting under the supervision of the World Bank. The participants in this assessment were Emmanuel Mathias (LEG, mission chief), Chady El Khoury (LEG), Habib Hitti (expert under the supervision of the LEG), and André Cuisset (expert under the supervision of the World Bank). The experts analyzed the institutional framework, laws, regulations, guidelines, and obligations with respect to AML/CFT, as well as the regulatory system or other systems in effect to combat money laundering and terrorist financing within financial institutions and DNFPBs . The adequacy, implementation, and effectiveness of all these mechanisms were also evaluated. This report provides a summary of the AML/CFT measures in effect in the Union of the Comoros on the date of or shortly after the on-site visit. It describes and analyzes these measures, indicates the level of the Union of the Comoros compliance with the 40 + 9 FATF Recommendations (See Table 1), and makes recommendations on measures to be taken to strengthen certain aspects of the system